(untitled) (Journal of Education and Development, 2019)
The study was to investigate students’ perception of lecturers in utilizing Information and Communication Technology (ICT) tools in instructional delivery in science education programme in Akwa Ibom State University. The researchers adopted descriptive survey design for the study. The population of the study which also formed the sample for the study were one hundred and thirty eight year three students of the Science Education Department, Akwa Ibom State University, Ikot Akpaden, Mkpat Enin L. G. A. Two research questions were formulated to guide the study. A questionnaire titled “Students’ Perception of Lecturers Utilization of Information and Communication Technology Tools Questionnaire (SPLUICTTQ) was used for data collection. The researchers personally administered the questionnaire to the students (respondents) and retrieved immediately after completion. The data was analysed using percentages. The results indicated that students’ perception of lecturers’ use of email and computer in instructional delivery is 36.23% and 34.78% higher than all other ICT tools. The result also revealed excellent utilization of internet and email for instructional delivery as shown in the table with 53.52% and 60.80% respectively, while audio tapes and computer were averagely used with 44.20% and 42.28% respectively as ICT tools in instructional delivery. The result showed that 44.26% was the perceived percentage of lecturers not using teleconferencing at all. It was concluded that the recommendations of school net (2006) and that of National Policy on Education on the use of ICT tools in instructional delivery be re-emphasized to encourage lecturers in the Department of Science Education on the use of ICT tools for effective instructional delivery process.